Formation of a military cooperation between Kazakhstana and the People’s Republic of China - Aрзыкулов A. A.; Орaзбековa Г. Р. (Journal of Oriental Studies, 2018)
At the end of the XX century with disintegration of the Soviet Union the new independent states appeared. The Republic of Kazakhstan is one of them. China one of the first recognized independence of Kazakhstan and established equal diplomatic relations. In work process of forming of a cooperation in military area between PK and People’s Republic of China is considered. Objective assessment of a military and technical cooperation between two countries allows to create the correct istorichesy representations of civil inhabitants and military specialists of the friendly countries.